A Quasi-Experimental Study of Medicaid Expansion and Urban Mortality in the American Northeast - Ayubcha, Cyrus; Pouladvand, Pedram; Ayubcha, Soussan (Frontiers in Public Health, 2021)
Objectives: To investigate the association of state-level Medicaid expansion and non-elderly mortality rates from 1999 to 2018 in Northeastern urban settings. Methods: This quasi-experimental study utilized a synthetic control method to assess the association of Medicaid expansion on non-elderly urban mortality rates (1999-2018). Counties encompassing the largest cities in the Northeastern Megalopolis (Washington D.C., Baltimore, Philadelphia, New York City, and Boston) were selected as treatment units (n=5 cities, 3,543,302 individuals in 2018). Cities in states without Medicaid expansion were utilized as control units (n=17 cities, 12,713,768 individuals in 2018). Results: Across all cities, there was a significant reduction in the neoplasm (Population-Adjusted Average Treatment Effect = -1.37 [95%CI -2.73, -0.42]) and all-cause (Population-Adjusted Average Treatment Effect = -2.57 [95%CI -8.46, -0.58]) mortality rate. Washington D.C. encountered the largest reductions in mortality (Average Treatment Effect on All-Cause Medical Mortality=-5.40 monthly deaths per 100,000 individuals [95%CI -12.50, -3.34], -18.84% [95%CI -43.64%, -11.67%] reduction, p=<0.001; Average Treatment Effect on Neoplasm Mortality=-1.95 monthly deaths per 100,000 individuals [95%CI -3.04, -0.98], -21.88% [95%CI -34.10%, -10.99%] reduction, p=0.002). Reductions in all-cause medical mortality and neoplasm mortality rates were similarly observed in other cities. Conclusion: Significant reductions in urban mortality rates were associated with Medicaid expansion. Our study suggests that Medicaid expansion saved lives in the observed urban settings.